E-book for IT experts learning English - Pešut, Darija (Array, 2011)
Living in this age of technology, where knowledge and information are just a click away, the authors wish to present an e-book which would be used for teaching English for Specific Purposes (ESP) at the College for Information Technology in Zagreb, Croatia. The article gives a detailed explanation of the idea and purpose of such a book. The contents and a possible software solution are also given. The results of a survey conducted at the mentioned college, among the students of the first year, are shown. The function of the book in education of IT professionals is commented and a firm conclusion, based on practical work with IT students, is made.